2015
DOI: 10.1038/srep10010
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-mediated impact on HIV infection in humanized BLT mice

Abstract: Cocaine abuse has been shown to have broad-ranging effects on human immunity. With regards to HIV infection, in vitro studies have shown that cocaine enhances infection of stimulated lymphocytes. Moreover, cohort studies in the pre- and post-HAART era have linked stimulant abuse with increased HIV pathogenesis. The latter data, however, have been undermined by a series of confounding factors underscoring the importance of controlled in vivo models to fully assess the impact of cocaine use and abuse on HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In vivo studies on the interactions between cocaine and HIV-1 under physiologic conditions have been conducted in a human-mouse hybrid model (huPBL-SCID mouse; Roth et al, 2002 , 2005 ; Kim et al, 2015 ). In this model, cocaine administration led to enhanced HIV-1 infection and a significant rise in circulating virus load ( Roth et al, 2002 , 2005 ; Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies on the interactions between cocaine and HIV-1 under physiologic conditions have been conducted in a human-mouse hybrid model (huPBL-SCID mouse; Roth et al, 2002 , 2005 ; Kim et al, 2015 ). In this model, cocaine administration led to enhanced HIV-1 infection and a significant rise in circulating virus load ( Roth et al, 2002 , 2005 ; Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies in a humanized mouse model revealed that cocaine significantly enhanced HIV-1 infection and increased the circulating viral load1719. Several in vitro studies have demonstrated enhanced HIV-1 infection and replication in T-cells and monocyte-macrophages in the presence of cocaine1314152021.…”
mentioning
confidence: 99%
“…Both cocaine and HIV target the CNS. Besides promoting HIV replication, cocaine primes the cells to become more susceptible for HIV infection [3133]. Within a few days of infection, HIV establishes a reservoir in the CNS by infecting different types of brain cells including resident microglial cells and astrocytes, along with visiting macrophages, and lymphocytes [31, 32, 3437].…”
Section: Cns Is the Common Target For Cocaine And Hivmentioning
confidence: 99%
“…Thus, illicit drug using HIV patients are more prone to the HIV associated comorbidities. Furthermore, the direct correlation of cocaine use with enhanced HIV replications has been well documented by several investigations using HIV infected humanized mouse models [32, 33, 49]. Hence, drug addiction extraordinarily contributes to the health and financial burden on HIV patients and the society as a whole [5, 6].…”
Section: Cns Is the Common Target For Cocaine And Hivmentioning
confidence: 99%